Transition between fast and slow gamma modes in rat hippocampus area CA1 in vitro is modulated by slow CA3 gamma oscillations. (2nd January 2014) - Pietersen, Alexander N. J.; Ward, Peter D.; Hagger‐Vaughan, Nicholas; Wiggins, James; Jefferys, John G. R.; Vreugdenhil, Martin
Abstract : Key points: The synchronisation of neuronal activity at gamma frequencies (30–100 Hz) could determine the effectiveness of neuronal communication. Gamma oscillations in the CA1 region of the hippocampus in vitro was thought to be dependent on gamma oscillations generated in area CA3, but in vivo CA1 can generate gamma oscillations independently. In this study we found that activating acetylcholine receptors induced stable gamma oscillations in the CA1 local network isolated in slices in vitro that were faster than those in CA3, but relied on similar neuronal circuitry involving feedback inhibition. Gamma frequency inputs from CA3 (spontaneous in intact hippocampal slices or stimulated in isolated CA1) can suppress the local fast gamma oscillation in CA1 and force it to adopt the slower CA3 oscillation through feed‐forward inhibition. This modulation could allow CA1 to alternate between effective communication with the entorhinal cortex and CA3, which may regulate memory encoding and memory recall phases. Abstract: Hippocampal gamma oscillations have been associated with cognitive functions including navigation and memory encoding/retrieval. Gamma oscillations in area CA1 are thought to depend on the oscillatory drive from CA3 (slow gamma) or the entorhinal cortex (fast gamma). Here we show that the local CA1 network can generate its own fast gamma that can be suppressed by slow gamma‐paced inputs from CA3. Moderate acetylcholine receptor activation induces fast (45 ± 1 Hz) gamma in rat CA1 minislices and slow (33 ± 1 Hz) gamma in CA3 minislices in vitro . Using pharmacological tools, current‐source density analysis and intracellular recordings from pyramidal cells and fast‐spiking stratum pyramidale interneurons, we demonstrate that fast gamma in CA1 is of the pyramidal–interneuron network gamma (PING) type, with the firing of principal cells paced by recurrent perisomal IPSCs. The oscillation frequency was only weakly dependent on IPSC amplitude, and decreased to that of CA3 slow gamma by reducing IPSC decay rate or reducing interneuron activation through tonic inhibition of interneurons. Fast gamma in CA1 was replaced by slow CA3‐driven gamma in unlesioned slices, which could be mimicked in CA1 minislices by sub‐threshold 35 Hz Schaffer collateral stimulation that activated fast‐spiking interneurons but hyperpolarised pyramidal cells, suggesting that slow gamma frequency CA3 outputs can suppress the CA1 fast gamma‐generating network by feed‐forward inhibition and replaces it with a slower gamma oscillation driven by feed‐forward inhibition. The transition between the two gamma oscillation modes in CA1 might allow it to alternate between effective communication with the medial entorhinal cortex and CA3, which have different roles in encoding and recall of memory.